Multilevel Inverters with Imbricated Switching Cells, PWM and DPWM-Controlled - Ursaru, O.; Aghion, C. (Elektronika ir Elektrotechnika, 2010)
This paper analyzes the functioning of multilevel voltage inverters with imbricated switching cells, destined for high and very high-power applications. Based on the theoretic principles, it presents the functioning of the three-phase voltage inverter with three-level imbricated cells. The simulations based on the sinusoidal PWM and DPWM control strategies yielded results that showed the main advantages of this type of inverters.